(untitled) (International Journal of Food and Nutritional Sciences, 2023)
All the civilizations nurture, nourish and promote their respective cultures in their laps, yearn to produce some or the other vertical which may leave an eternal imprint on the sands of time. In the process, it is a general tendency that a select group of ideas are crystalized to form such a vertical and these verticals are expressed through the oral narrative traditions, or written textual traditions or some ritualistic practices, or, a combination of some or all of these. Bharat has been the cradle of civilization and is the only nation which can boast of an incessant flow of its oral, written, theoretical and practical traditions ever since the beginning of time. It has contributed numerous ideas which have shaped the civilizations in myriad forms and through different expressions of these esoteric as well as exoteric concepts. Yoga is one such concept which has been revered as one of the principle philosophical schools of Bharat and which is a living tradition even today as has been proclaimed by the UNESCO as the International Yoga Day on 21st of June every year since the year 2015.